Eksistensi Tradisi Menyilaq pada Masyarakat Suku Sasak di Tengah Gempuran Teknologi Informasi Modern - Suhadah Suhadah; Fathurrijal Fathurrijal; Cucu Cahyanti; Baiq Ida Astini (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2026)
The rapid development of modern information technology has transformed human communication from face-to-face interactions to mediated digital relations. This study aims to examine the existence of the